Social factors conditioning the tourist activity and destinations of Chicago Polonia - Ziółkowska-Weiss, Kamila (Turyzm/Tourism, 2017)
Staying in social groups is inseparably connected with the process of socialization and upbringing. Educational environments play a significant role in shaping human attitudes, including those towards tourist activity. Family and school are part of those educational environments whose impact is of a special nature. The main objective is to present the social factors conditioning tourist activity and destinations among Chicago Polonia. Among these factors, the family situation, family patterns, a lack of family tradition, membership of an organization, an individual desire to discover new places and a lack of free time have been distinguished. The aim is to check whether affiliation to an organization influences a greater frequency of tourist trips of Chicago Polonia and whether it has an impact on the choice of tourist destination.